Impact of Green Banking Initiatives on Banks’ Profitability A Comparative Study of Public, Private and Foreign Banks - M. Ramila and S. Gurusamy (Commerce Spectrum, 2015)
In the present scenario, banking industry is playing a vital role in the sustainable development of the world. In this respect, the RBI has introduced the new concept called “Green Banking”. In India, most of the banks implement green banking in their operations. This paper investigates as to how green banking initiatives such as NEFT, RTGS, ECS, ATM, POS and Mobile banking impact the profitability of public sector banks, private sector banks and foreign banks. To achieve this objective, the hypotheses were framed and the study has found that among the three banking sectors, private sector banks deliver good performance in the form of adopting green banking initiatives such as RTGS, ECS, Mobile banking and NEFT transactions as compared to public sector and foreign banks.